Method to estimate the effective temperatures of late-type giants using line-depth ratios in the wavelength range 0.97–1.32 μm. Issue 4 (23rd November 2017) - Taniguchi, Daisuke; Matsunaga, Noriyuki; Kobayashi, Naoto; Fukue, Kei; Hamano, Satoshi; Ikeda, Yuji; Kawakita, Hideyo; Kondo, Sohei; Sameshima, Hiroaki; Yasui, Chikako
Abstract: The effective temperature, one of the most fundamental atmospheric parameters of a star, can be estimated using various methods; here, we focus on a method using line-depth ratios (LDRs). This method combines low- and high-excitation lines and makes use of relations between LDRs of these line pairs and the effective temperature. It has an advantage, for example, of being minimally affected by interstellar reddening, which changes stellar colours. We report 81 relations between LDRs and effective temperature established with high-resolution, λ/Δλ ∼ 28 000, spectra of nine G- to M-type giants in the Y and J bands. Our analysis gives the first comprehensive set of LDR relations for this wavelength range. The combination of all these relations can be used to determine the effective temperatures of stars that have 3700 <  T eff  < 5400 K and −0.5 < [Fe/H] < +0.3 dex, to a precision of ±10 K in the best cases.